"An apple a day keeps the doctor away": The potentials of apple bioactive constituents for chronic disease prevention. Issue 6 (3rd May 2022) - Oyenihi, Ayodeji B.; Belay, Zinash A.; Mditshwa, Asanda; Caleb, Oluwafemi J.
Abstract: Apples are rich sources of selected micronutrients (e.g., iron, zinc, vitamins C and E) and polyphenols (e.g., procyanidins, phloridzin, 5′‐caffeoylquinic acid) that can help in mitigating micronutrient deficiencies (MNDs) and chronic diseases. This review provides an up‐to‐date overview of the significant bioactive compounds in apples together with their reported pharmacological actions against chronic diseases such as diabetes, cancer, and cardiovascular diseases. For consumers to fully gain these health benefits, it is important to ensure an all‐year‐round supply of highly nutritious and good‐quality apples. Therefore, after harvest, the physicochemical and nutritional quality attributes of apples are maintained by applying various postharvest treatments and hurdle techniques. The impact of these postharvest practices on the safety of apples during storage is also highlighted. This review emphasizes that advancements in postharvest management strategies that extend the storage life of apples should be optimized to better preserve the bioactive components crucial to daily dietary needs and this can help improve the overall health of consumers.